Hot Topics and Frontier Evolution of Game In Stem Learning Research: A Bibliometric Mapping from 2002 to 2022 - Novia Novia; Riandi Riandi; Anna Permanasari; Ida Kaniawati (Universitas Kanjuruhan Malang, 2022)
The aim of the present study is to explore the evolving trend of research directions in the field of game in STEM learning. This research uses Scopus search analysis, Microsoft Excel software, and VOS viewer software. Based on 1489 articles (488 selected documents) selected from Scopus indexed journals, co-authorship, co-citation, co-occurrence, cluster, and content analysis were conducted. The results of the quantitative analysis showed that hugely important work on games of STEM education, namely computer game and digital game base learning. The literature on games in STEM education has explored fourteen hot themes during the last couple of decades: STEM, digital game, active learning, game based learning, game, project based learning, serious game, creative self efficacy, teaching concept, learning content, industri 4.0, STEM activities, game element, and interactive learning environment. The bibliometric study conducted gives a thorough and complete picture of STEM education research that may be valuable for scholars interested in furthering future understanding in this field.